Multipath Routing for Dual-Radio Wireless Sensor Networks - Ribeiro Júnior, Nildo; Vieira, Marcos; Vieira, Luiz (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2018)
The design of a Wireless Sensor Network depends signiﬁcantly on the application. For the traditional applications, such as environmental monitoring, smart buildings or agriculture, the design prioritized reducing the cost, the energy expenditure and memory usage at the expense of not having a higher throughput. Modern applications, such as surveillance or trafﬁc monitoring, usually require using cameras and transmitting video data through the network. For such applications, dual-radio platforms were developed where their design prioritizes achieving higher throughput and conserve the energy efﬁciency of In this work, we propose a multipath routing algorithm to ﬁnd the network. two disjoint paths with the same parity between a pair of nodes in the network. The new routing algorithm, combined with a forwarding scheme that alternates the radios throughout the paths, allows all nodes in the paths to use both radios in parallel all the time, doubling the throughput in comparison with a single path routing scheme. We evaluated our algorithm and forwarding scheme in a real world testbed with 100 nodes of the Opal dual-radio platform. Our scheme were able to double the throughput when compared with FastForward, the state-of-the-art protocol for dual-radio platforms, and achieve up to 96% of the theoretical limit.